Exclusion clauses in standard form consumer contracts under Malaysian and Islamic law - Abu Bakar, Elistina; Amin, Naemah (Yayasan Dakwah Islamiah Malaysia, 2015)
The aim of this paper is to explore the Islamic law of muamalat as the tools of consumer protection in dealings with exclusion clauses. The underlying philosophy under the Malaysian law is that consumers are free to enter into contracts and therefore must take care of their own interest. This principle, which is based on the assumption of equal bargaining power between parties, though, is not appropriate when consumers are involved. The law of contract, common law and the Consumer Protection Act 1999 are insufficient to tackle the issue of exclusion clauses. On the other hand, Islamic law has provided various principles that protect consumers. The discussion under Islamic law is made under three important issues which are the freedom of contract, contract of adhesion (aqd al-idham) and the sale of bara’a (absolution).